2018
DOI: 10.1002/pc.24753
|View full text |Cite
|
Sign up to set email alerts
|

The use of upconversion microparticles as a novel internal radiation source for fabrication of composite materials

Abstract: Upconversion (UC) microparticles were used as novel internal radiation sources for composite preparation. These particles emit Ultraviolet-Visible radiation when exposed to Near-infrared waves. This radiation causes uniform and deep polymerization. Two types of UC particles were prepared via a facile hydrothermal method, including NaLuF 4 : Yb 20%, Tm 0.5% and NaLuF 4 : Yb 40%, Tm 0.5%. The effect of three different photoinitiator systems, including titanocene, bisacylphosphine oxide, and camphorquinone, on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…also reported that the curing depth could be increased from 0.5 cm to 3 cm (Figure 5c). In addition, the monomer conversion was improved from 25 % to around 75 % (Figure 5d) when the laser power was increased from 1.5 W to 4.5 W [52] . However, it should be notable that the excited levels of activator ions would be saturated and the emission intensity reaches maximum when the laser power exceeds a certain threshold.…”
Section: Optimization Of Nir Polymerizationmentioning
confidence: 95%
See 4 more Smart Citations
“…also reported that the curing depth could be increased from 0.5 cm to 3 cm (Figure 5c). In addition, the monomer conversion was improved from 25 % to around 75 % (Figure 5d) when the laser power was increased from 1.5 W to 4.5 W [52] . However, it should be notable that the excited levels of activator ions would be saturated and the emission intensity reaches maximum when the laser power exceeds a certain threshold.…”
Section: Optimization Of Nir Polymerizationmentioning
confidence: 95%
“…As anticipated, the UC‐40 exhibited stronger upconversion luminescence than UC‐20 due to more absorption of incident NIR photons with higher concentration of sensitizer ions. As a result, the curing depth for UC‐40 is increased by a couple of times than that for UC‐20 (Figure 6a) [52] . Currently, the upconversion quantum yield of nano‐sized UCNPs is generally below 1 %, which is significantly lower than the micro‐sized counterparts.…”
Section: Optimization Of Nir Polymerizationmentioning
confidence: 96%
See 3 more Smart Citations